Motivasi Intrinsik Dan Ekstrinsik Siswa Ekstrakurikuler Bolavoli Di SMP Negeri 9 Surabaya - Alva Rizki Ramadhandy; Made Pramono (LPPM Politeknik Pratama, 2024)
Motivation is an encouragement that a person has to do something that is intended or desired. The background of this study is that the researcher saw an increase in extracurricular bolavoli participants at SMP Negeri 9 Surabaya from 2022. Volleyball extracurricular activities are held 1x a week, students who take part in extracurricular activities always attend these exercises on Tuesdays without missing a single exercise not to attend, this proves that students have a strong interest and encouragement in participating in volleyball extracurricular activities at SMP Negeri 9 Surabaya. The purpose of this study was to determine the level of intrinsic and extrinsic motivation of extracurricular volleyball students at SMP Negeri 9 Surabaya. This study uses a quantitative descriptive type using a survey method, whose data is taken with a questionnaire. This study involved all students of SMP Negeri 9 Surabaya who participated in extracurricular volleyball activities totaling 30 students. This research was conducted on June 20, 2023 at SMP Negeri 9 Surabaya, using the total sampling technique. The results of this study in the intrinsic motivation factor show that volleyball extracurricular students at SMP Negeri 9 Surabaya are in the